Pengembangan Kreativitas dan Keterampilan Mahasiswa Dengan Praktek Pembuatan Bakpia Sebagai Bentuk Pembelajaran Eksperiential Learning di PT. Juwara Satoe Melalui Kegiatan KKL - Janusi Waliamin; Reivaldy Fikrie; Yulia Nur Halimah; Dion Caisar Efriatmoko; Irma Ningsi; Raden Muhamad Ilham; Flora Cinta (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The objective was to analyze the development of students' creativity and skills through practical industrial experience. A descriptive approach was employed using experiential learning stages, including direct experience, observation, reflection, and knowledge appl ication. Activities consisted of company presentations and hands-on bakpia production practice. The results indicated improvements in students' understanding of production processes, technical skills, creativity, and teamwork abilities. Students also gained insights into business management and entrepreneurial opportunities in the culinary sector. The findings demonstrate that experiential learning effectively enhances student competencies by integrating theoretical knowledge with practical experience. Therefore, bakpia production practice in the Field Work Practice program can serve as an alternative learning method to support the development of students' skills and creativity.